2016
DOI: 10.5755/j01.eie.22.6.13474
|View full text |Cite
|
Sign up to set email alerts
|

Distributed Hybrid Spectrum Access for Cognitive Femtocells in 5G Mobile Networks

Abstract: The femto access points (FAPs) with cognitive capabilities, also known as cognitive FAPs, are able to efficiently mitigate interference in two-tier heterogeneous networks. Hence, the concept of cognitive FAPs can be seen as one of the key enablers for future 5G networks, where high density of FAPs is foreseen. However, conventional overlay and underlay spectrum sharing strategies enabling the cognitive FAPs to access spectrum of macrocells have several drawbacks. The main disadvantage of the former one is that… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2018
2018
2020
2020

Publication Types

Select...
1
1

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 21 publications
0
1
0
Order By: Relevance
“…In [6], the authors have suggested a spectrum sharing technique which is shown to be very useful for throughput performance of small and macro cell users. In [7], authors propose a power economic mechanism and analyse the scheme to show that heavily deploying low power small cells can influence power spending.…”
Section: Literature Reviewmentioning
confidence: 99%
“…In [6], the authors have suggested a spectrum sharing technique which is shown to be very useful for throughput performance of small and macro cell users. In [7], authors propose a power economic mechanism and analyse the scheme to show that heavily deploying low power small cells can influence power spending.…”
Section: Literature Reviewmentioning
confidence: 99%